Games and playthings in a child day care center: a bioecological approach - Rute Estanislava Tolocka; Ana Lucia Brollo (Universidade Federal de Santa Catarina, 2010)
Social changes have contributed to decreased opportunities for children to perform physical activities. Children have been introduced in preschools where the opportunities of playing are insufficient, thus being deprived of the benefits of such activity. The aim of this study was to analyze the relationship between ludic physical activities and child development. A descriptive study was conducted on 68 children of both genders, aged 4 to 6 years, from a public child day care center. A physical education program was offered twice per week and an event involving other children was carried out. Activities, social roles, interpersonal relations, emotions, and personal characteristics were analyzed. Improvement was observed in interpersonal relations and social relationships, as well as in emotional control. Basic emotions and different child characteristics were expressed. Thus, the introduction of games and playthings at school may contribute to child development and to the engagement of children in physical activities.